The Role of Institution and Macroeconomic Policy Mix on Economic Growth in Muslim Country - Muhammad Ghafur Wibowo; Hadri Kusuma; Ibnu Qizam (Universitas Muhammadiyah Yogyakarta, 2022)
This study examines the role of the fiscal and monetary policy mix on economic growth with the St. model. Louis, which Andersen and Jordan developed in 1968, included the variable quality of institutions (governance) as a moderator. This research model uses the independent variable in the form of money supply (M) as a proxy for monetary policy and government expenditure (G) and government debt (D) as a proxy for fiscal policy. The governance index variable (INS) consists of 6 indicators, namely 1). Voice and Accountability; 2). Political Stability and Absence of Violence/Terrorism; 3). Government Effectiveness; 4). Regulatory Quality; 5). Rule of Law; 6). Control of Corruption. The objects of this research are all member countries of the Organization of the Islamic Conference (OIC), 57 countries. Due to the limited data that can be accessed, 46 countries were selected as research samples with a research period of 2005-2018. The analytical tool used in this study is a moderating panel data regression consisting of 28 equations. This study indicates that fiscal policy (government expenditure) and monetary policy (money supply) have a significant effect on economic growth. The government debt has a negative effect on economic growth in OIC countries. The quality of governance has a positive effect on economic growth in the OIC countries. This shows the important role of the quality of governance in the economy, as in the latest economic growth theory. The quality of governance cannot moderate the effect of the fiscal and monetary policy mix on economic growth in the OIC countries. The governance index plays a more direct role in economic growth, not as an effective moderator for government economic policies. The governance index is more effective in moderating various economic variables, which are private economic activities.